Sublingual Lymph Node Metastasis in Early-Stage Floor of the Mouth Carcinoma - İsa Kaya; Kerem Öztürk; Göksel Turhal (Turkish Archives of Otorhinolaryngology, 2017)

(untitled)
Metastasis to the sublingual lymph nodes is very rare in oral cavity cancers. We present an early-stage floor of the mouth (FOM) cancer case with metastasis to the sublingual lymph node. Even though the rate of metastatic sublingual lymph nodes is low, the uncommon presence of sublingual lymph node metastasis in an early-stage FOM cancer case raises the question of routine FOM dissection. Further anatomic and pathologic studies addressing the rate and pattern of sublingual lymph node metastasis are warranted.